Analisis Rasio Likuiditas, Solvabilitas, dan Profitabilitas Untuk Mengukur Kinerja Keuangan Pada PT Martina Berto Tbk Periode 2014-2018 - Nida Auliana Umami; Ayu Febriyanti Safitri (Jurnal Riset Bisnis dan Investasi, 2021)
Financial statement analysis is one way to find out the condition of the company, financial ratios are one of the tools used to analyze financial statements. The purpose of this study is to determine the financial condition through the analysis of liquidity ratios, solvency, and profitability as well as the constraints that occur in financial performance and solutions made by the company. The method used in this research is descriptive method. The data was studied in the form of financial statements of PT. Martina Berto Tbk for 2014-2018. Based on the results, it can be concluded that the liquidity ratio is healthy because the current, fast, and INWC ratio is above the industry standard. The solvency ratio is healthy because the debt to equity ratio and LTDtER are above the standard. While the profitability ratios are declared unhealthy because the ratios of NPM, ROA, and ROE are below the standard.